Pensamientos automáticos y autoestima de los adolescentes que sisten a dermatología del Hospital Provincial General Docente Riobamba, período septiembre 2015-febrero 2016. - Arias Escudero, Edison Alejandro (2016)
This research takes as its theme "automatic thoughts and self-esteem of adolescents attending dermatology Provincial General Teaching Hospital Riobamba, period September 2015 - February 2016", it aims to analyze the influence of automatic thoughts on self-esteem of adolescents ; in which we worked with all adolescents who were diagnosed with acne, with a population of 108 and a sample of 25, which were selected on the criterion of attending for the first time dermatologic consultation. The research was conducted under the scientific method, quantitative and experimental designs not addressed, the type of field research was used, documentary and transversal, and the level of research used was descriptive. The techniques and instruments of data collection were used: "Inventory of automatic thoughts (Ruíz and Lujan)" and "Self Esteem: Self-Exam Cirilo Toro Vargas".